Peran Guru PAI dalam Menanamkan Nilai-nilai Islam Wasatiyah Siswa - Jentoro, Jentoro; Yusro, Ngadri; Yanuarti, Eka; Karolina, Asri; Deriwanto, Deriwanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine how the role of PAI teachers in instilling Islamic values ​​in Wasatiyah in SMP N 31 Rejang Lebong, then to find out what factors influence the planting of Islamic values ​​in Wasatiyah. This type of research is field research using a qualitative approach, the data sources are Islamic religious education teachers, principals and students. Data collection techniques using observation, interviews and documentation. The results showed, there are 3 components of the role of PAI teachers in instilling the values ​​of Islam Wasatiyah namely; First, in instilling the values ​​of Islam Wasatiyah the teacher acts as a motivator, administrator and evaluator; The two supporting factors in instilling Wasatiyah Islamic values ​​in students are the participation and role of parents in guiding their children by instilling Islamic wasatiyah values ​​and technological advances in obtaining information; Third, inhibiting the role of PAI teachers in instilling the values ​​of wasatiyah Islam, among others, is not wise of students to choose content that is useful in utilizing the technology provided, such as improper use of the internet. In conclusion, the role of PAI teachers in instilling the value of Islamic Watasyah is as a motivator, as an administrator and as an evaluator, which is also influenced by the role of parents and the use of information that is growing rapidly among students. Keywords: Teacher's Role, PAI, Wasatiyah Islamic Values